Empleo del algoritmo de colonia de hormigas para la sintonización de un controlador pid aplicado a un circuito rc - Garcia Pereda, Jorge Pablo (2018)
The development of this thesis entitled "Use of the algorithm of ant colony for the tuning of a PID controller applied to an RC circuit", aims to implement a program based on the multi object ant colony algorithm with restrictions as a method to tune a PID controller applied to a first-order RC circuit, and evaluate its performance by comparing it with conventional tuning methods such as the Ziegler and Nichols reaction curve method and Matlab's PID Tuner tool. For the execution of the experimental tests, a control system was implemented, which basically consists of an RC circuit, with a resistance of 10 KΩ and an electrolytic capacitor of 470 uF; a data acquisition card which consists of an Arduino Uno board and an MCP 4725 digital analog converter; and the Labview software which was programmed to be used as a PID controller. To perform the simulations of the RC circuit control system, the Matlab Simulink tool was used. The mathematical model of the RC circuit was obtained by means of the experimental identification method and the results show that said model adequately represents the circuit. An adjustment or fit percentage of 99.41% was obtained and the model identified is that of a pure first order system with a static gain of 0.997 and a time constant of 4.69 sec. The results show that with regard to the conventional tuning methods (reaction curve and PID Tuner) the multiobject ant colony algorithm with restrictions has the lowest maximum overshoots for the entire range of adjustment points studied (0 to 4 vdc). Regarding the establishment time, this method obtained the lowest values for the range of adjustment points from 0 to 1 vdc.